MODELING OPEN AIR AND SHADE DRYING OF CORYMBIA CITRIODORA LEAVES FOR THE ESSENTIAL OIL PRODUCTION - Makomo, Hubert; Bassiloua, Jean Bruno; Bivoumboukoulou, Fergie Romance; Silou, Thomas (International Journal of Research -GRANTHAALAYAH, 2021)
In the literature, the drying mechanism were generally analyzed in terms of effective diffusivity through the pseudo first order diffusion model. This process was revisited through the modified Peleg model, assuming the drying as a moisture desorption versus drying time. The leaves of Corymbia citriodora acclimatized in the Congo Brazzaville “Plateau des Cataractes” were dried in open air and under shade thanks to a domestic scale of essential oil production. One obtains following model parameters: kinetic constant k1: 0.8555 - 2.1355 d.(g/g)-1, extraction capacity constant K2: 1.5255 - 1.8733 (g/g)-1; end equilibrium moisture X∞ = 0.53 - 0.66 g/g. and first order drying kinetic constant k = K2/k1: 1.71 - 1.78 d-1. Pseudo first order diffusion model fits experimental data with k = 0.368 - 0.587 d-1 and t1/2 = 1,18 - 1,88 d.. These results needed for the optimization of proccess and sizing equipments came from a fast graphic data processing, with low computer inputs.